SEMIOTIKA MITOLOGIS SEBUAH TINJAUAN AWAL BAGI ANALISIS SEMIOTIKA BARTHESIAN - Urfan, Noveri Faikar (Universitas Teuku Umar, 2018)
Roland Barthes is widely known as a semiotic figure who succeeded in renewing the thoughts of his predecessor Ferdinand de Saussure by introducing the concept of myth. Myth is a second level of signification system, which is built from reading the first level sign. Barthes considers that the reading of signs does not stop at the level of denotative meaning, but also needs to be directed to probe the connotative meaning that is hidden or which is often unconscious behind the object. Reading the signs to the level of myth is also an attempt to dismantle the existence of ideology. Ideology in the context of reading signs is interpreted as a forced meaning to be accepted as something natural. In the end, reading the signs in Roland Barthes's approach challenges us to apply them to reading contemporary objects such as advertising, photography, film and others. Sign readers are challenged to combine interpretive models on two levels, namely reading denotative meanings in reading language levels and connotative meanings in reading mythical levels. Keywords: Roland Barthes, Semiotic, Significancy System, Myth